2001
DOI: 10.1093/bja/87.4.602
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity and density of common anaesthetic gases: implications for flow measurements

Abstract: Although viscosity (mu) is a crucial factor in measurements of flow with a pneumotachograph, and density (rho) also plays a role in the presence of turbulent flow, these material constants are not available for the volatile anaesthetic agents commonly administered in clinical practice. Thus, we determined experimentally mu and rho of pure volatile anaesthetic agents. Input impedance of a rigid-wall polyethylene tube (Zt) was measured when the tube was filled with various mixtures of carrier gases (air, 100% ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 10 publications
(9 reference statements)
0
22
0
Order By: Relevance
“…Previously, Habre et al [12] characterized changes in the physical properties of gas mixtures for various concentrations of volatile anesthetics, and concluded that clinically relevant concentrations significantly affected estimates of ρ ( i.e ., up to 48% deviation compared to room air), but only marginally affected estimates of μ ( i.e ., less than 4% deviation compared to room air). Following these principal findings, Miyaji et al [4] demonstrated that ventilation with sevoflurane and desflurane altered delivered V T for feedback-control conditions determined using a variable orifice flow sensor.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previously, Habre et al [12] characterized changes in the physical properties of gas mixtures for various concentrations of volatile anesthetics, and concluded that clinically relevant concentrations significantly affected estimates of ρ ( i.e ., up to 48% deviation compared to room air), but only marginally affected estimates of μ ( i.e ., less than 4% deviation compared to room air). Following these principal findings, Miyaji et al [4] demonstrated that ventilation with sevoflurane and desflurane altered delivered V T for feedback-control conditions determined using a variable orifice flow sensor.…”
Section: Discussionmentioning
confidence: 99%
“…The PNT is commonly used in research settings for accurate flow measurement during mechanical ventilation [12, 1719]. The PNT measures a differential pressure across a calibrated resistive element, and assumes that the relationship between ∆ P and V̇ is linear and dependent on μ, but not on other gas properties such as ρ, k , and c p [12, 17].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations